Perancangan Dan Simulasi Aerodinamis Bodi Mobil Balap Formula Anobrain Singaperbangsa Ev Menggunakan Komputasi Dinamika Fluida - Darpito, Muhammad Herjuno (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2025)
Aerodynamics is a branch of dynamics that studies the movement of air flows, especially when the air interacts with solid objects or vehicles. In the aerodynamics of a racing car, the most important thing for a car to go fast is to reduce the drag force as small as possible by increasing lift force and downforce as much as possible. Modelling the aerodynamics body shape of the Formula Anobrain Singaperbangsa EV racing car can have an impact on reducing battery usage and minimizing darg force that hinder the speed of the racing car. The aim of this research was to find out whether the body of the Formula Anobrain Singaperbangsa EV racing car when traveling at a speed of 6,94444 m/s, 13,8889 m/s, 20,8333 m/s, 27,7778 m/s was covergent and to find out darg force value is smaller than lift force and downforce values on the racing car body and looks at the air flow characteristics based on velocity streamline, velocity contours and pressure contours. The research methodology used is computational fluid dynamics simulation using Ansys 2021 R2 software